Intestinal Microbiota and Lymphoma - L. Yamamoto, Mitsuko; Westbrook, Aya; H. Schiestl, Robert (Journal of Nutritional Therapeutics, 2016)
The intestinal microbiota and gut immune system must constantly communicate to maintain a balance between tolerance and activation: on one hand, our immune system should protect us from pathogenic microbes and on the other hand, most of the millions of microbes in and on our body are innocuous symbionts and some can even be beneficial. Since there is such a close interaction between the immune system and the intestinal microbiota, it is not surprising that some lymphomas such as mucosal-associated lymphoid tissue (MALT) lymphoma have been shown to be caused by the presence of certain bacteria. Animal models played an important role in establishing causation and mechanism of bacteria-induced MALT lymphoma. In this review we discuss different ways that animal models have been applied to establish a link between the gut microbiota and lymphoma and how animal models have helped to elucidate mechanisms of microbiota-induced lymphoma. While there are not a plethora of studies demonstrating a connection between microbiota and lymphoma development, we believe that animal models are a system which can be exploited in the future to enhance our understanding of causation and improve prognosis and treatment of lymphoma.